2014
DOI: 10.1002/2014jd022065
|View full text |Cite
|
Sign up to set email alerts
|

Initial results of LF sensor network for lightning observation and characteristics of lightning emission in LF band

Abstract: We have been developing an LF sensor network called Broadband Observation network forLightning and Thunderstorm (BOLT), to image the structure of lightning discharges in 3D using time of arrival (TOA) technique. This paper documents initial results and characteristics of BOLT source locations for further understanding of LF radiation associated with lightning. Theoretical reduced Chi-square distribution fitted to BOLT observation data indicates a root mean square (rms) timing error of about 200 ns for each sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 53 publications
5
62
0
Order By: Relevance
“…The LF sensor array in the current study is quite similar to that deployed by Yoshida et al . []. Monte Carlo simulations (not shown) for the estimation of BOLT location errors in the current study array indicate similar location errors to those reported by Yoshida et al .…”
Section: Instrumentationmentioning
confidence: 98%
See 1 more Smart Citation
“…The LF sensor array in the current study is quite similar to that deployed by Yoshida et al . []. Monte Carlo simulations (not shown) for the estimation of BOLT location errors in the current study array indicate similar location errors to those reported by Yoshida et al .…”
Section: Instrumentationmentioning
confidence: 98%
“…[]. We update the locating algorithm described in Yoshida et al [], where we apply a band‐passed digital filter with a passband of 230–500 kHz before identifying the pulse peaks in the LF records, succeeding in producing much more BOLT source locations than those in the previous location algorithm. In this study, the BOLT source location is estimated based on seven or more stations.…”
Section: Instrumentationmentioning
confidence: 99%
“…Time‐of‐arrival technique was employed to obtain 3‐D locations of lightning discharges as described in Yoshida et al . [].…”
Section: Experiments and Datamentioning
confidence: 99%
“…Radiation sources often show horizontal layered structures inside clouds related to intra-cloud (IC) and/or cloud-to-ground (CG) lightning discharges. Previous studies have demonstrated that these layers correspond to charge layers formed in clouds, and extended discussions of electrical characteristics based on that assumption have been published (Krehbiel et al, 1979;Williams, 1989: Bateman et al, 1999Shao and Krehbiel, 1996;Thomas et al, 2001;Coleman et al, 2003;Riousset et al, 2007;Yoshida et al, 2014). These results have demonstrated the usefulness of three-dimensional monitoring of lightning discharges using electromagnetic waves of VHF or other bands.…”
Section: Introductionmentioning
confidence: 69%